Food Security and Poverty Reduction: Study in Lamongan Regency East Java - Setyo Tri Wahyudi; Nurul Badriyah (Institute of Research and Community Service, University of Brawijaya)
Realizing food security in Indonesia is facing multidimensional problems and challenges in terms of economic aspects. Meanwhile, the challenges to achieve food security at the macro level are becoming increasingly difficult as the trend of food supply and demand is moving towards the opposite direction. In terms of supply, food supply is predicted to be increasingly difficult due to the physical, economical and environmental constraints on its growth. On the other hand, in terms of demand, it is predicted that food demand will continue to grow in line with the population growth, economic development, and the dynamics of the strategic environment.East Java has a great potential for supporting national food security due to its relative extent of agricultural land. In addition, the overflow of production factors in the form of land is the capital for East Java to develop the agricultural sector for improving food security. This study aims to describe the potential of food security and its relation to the efforts for reducing poverty in Lamongan. The results showed that rice, corn, and soybean commodities are the main commodities of agricultural food crop sector in Lamongan. These three commodities contribute and generate high productivity, in fact, does not affect the rate of poverty. Despite the various efforts performed, however, the increase in productivity has not been encouraging. Further, the Poverty Depth Index in Lamongan is precisely increasing. Therefore, Adult Equivalent (AE) method was used as a method to equalize child consumption needs with adult population by calculating the economic scale for calculating poverty rate. The results of the AE method revealed that the economic scale in adult categories needs to be prioritized on corn and soybean farmers.